Prognostic Values of Preoperative Inflammatory and Nutritional Markers for Colorectal Cancer - Zhang, Nannan; Ning, Feilong; Guo, Rui; Pei, Junpeng; Qiao, Yun; Fan, Jin; Jiang, Bo; Liu, Yanlong; Chi, Zhaocheng; Mei, Zubing; Abe, Masanobu; Zhu, Ji; et al. (Frontiers in Oncology, 2020)
Abstract Background: Increasing evidence indicates that inflammation and nutritional status are associated with survival outcomes in patients with colorectal cancer (CRC). This study aimed to investigate the prognostic values of preoperative inflammatory and nutritional factors and develop a prognostic model individually predicting overall survival (OS) and disease-free survival (DFS) in patients with CRC. Methods: We retrospectively collected data on patients with CRC who underwent radical surgery. Independent prognostic inflammatory and nutritional markers were identified and novel prognostic models were developed incorporating the identified factors. The discriminative ability and model-fitting performance were evaluated by receiver operating characteristic curves and Akaike information criteria. Clinical usefulness was assessed by decision curve analysis. Results: A total of 400 eligible patients were identified. Multivariate analysis identified pN stage, tumor differentiation grade, neutrophil count, and body mass index as independent prognostic factors for OS, and pN stage, tumor differentiation grade, neutrophil count, neutrophil-lymphocyte ratio, and serum albumin as prognostic factors for DFS. The combined inflammatory and nutritional prognostic model showed better discriminative ability, model-fitting performance, and net benefits than the inflammatory and nutritional models alone, and the American Joint Committee on Cancer (AJCC) 8th TNM classification for predicting OS and DFS. Conclusion: Preoperative nutritional and inflammatory factors have significant prognostic value in patients with CRC. A novel prognostic model incorporating preoperative inflammatory and nutritional markers provides better prognostic performance than the AJCC 8th TNM classification. A novel nomogram incorporating preoperative inflammatory and nutritional markers can individually predict OS and DFS in patients with CRC.